Relative efficiency, scale effect, and scope effect of public hospitals: evidence from Australia - Jian Wang; Zhong Zhao; Amir Mahmood (Institute for the Study of Labor (IZA), 2006)
Using the 1997-1998 New South Wales public-hospitals comparison data, we investigate the hospital-level inefficiency by applying a stochastic-frontier multiproduct cost function. We use a flexible translog cost function to reduce the measurement errors of the outputs of the hospital. The main findings are: First, inefficiency accounts for 9.3% of total hospital costs in large hospitals and 11.3% in small hospitals, when including complexity indicators. Second, diseconomies of scale exist in very large hospitals, whereas scale economies appear in very small hospitals. Third, scope effects are found in both large and small hospitals. Fourth, small hospitals are more labor-intensive than large hospitals are.
urn:nbn:de:101:1-20080502103
Keywords: 330